Technical and Ethical Challenges in the Care of an Independent Nonagenarian with Critical Limb Ischemia - Fereydooni, Arash; Dahl, Neera; Chaar, Cassius Iyad Ochoa (Archives of Clinical and Medical Case Reports, 2020)
Objective: Caring for elderly patients with peripheral artery disease is challenging given their complex anatomy and frail physiology. Despite advances in endovascular therapy, intervening on this patient population poses unique technical and ethical considerations. Present is a case that illustrates both the technical challenges and the ethical dilemma in the care of a 94-year old man with end stage renal disease treated for critical limb ischemia. Methods: The medical record of patient was reviewed. Results: Under local anesthesia and sedation, subintimal arterial flossing with antegrade-retrograde intervention was performed for recanalization of chronic total occlusion of superficial femoral artery. Patient healed his toe amputation wound at 5-week follow-up and was able to walk independently. Conclusion: Advances in endovascular therapy provide effective treatment of very old patients with CLI. Discussing and setting realistic expectations with patients and their families is crucial to ensure the elderly are provided with better quality of life.